PENGEMBANGAN SKALA KETERAMPILAN SOSIAL MAHASISWA PGSD - Budyartati, Sri (Premiere Educandum, 2014)
In Indonesia, social skills learning strategies into one of the specified component as a graduation requirement PPG (Professional Teacher Education). The policy as the aspect of the process that is weighted PPL large enough space that is 30 Placement assessment of social skills in the process of field practice, is the right decision, given the social skills can be seen clearly in the Program Particularly Student Conduct Study Elementary School Teacher and has implications reflecting broad holistic or overall competence, behavior is a person in general showed a tendency to someone in something.Keywords : Social skill scale development, Student of Primary Education.